Factors Affecting Mental Health Among Police Officers in the State of Kedah Malaysia - Kamaruddin, Saslina; Krishnan, Thamil Chelvan; Saufi, Nadia Nabila Mohd; Mohamad, Ani Munirah; Ikhsan, Muhammad Izwan (Medicine, Law & Society, 2025)
Mental health among law enforcement personnel has become a growing concern, raising questions about institutional responsibility and legal protections within the workplace. This study explores the factors influencing mental health among Royal Malaysian Police (RMP) members at IPK Kedah, focusing on legal and organizational implications. The research aims to identify key stressors and examine whether age and job rank correlate with psychological well-being, using a quantitative approach involving 100 respondents who completed structured questionnaires. Findings reveal that occupational stress is the leading contributor (mean = 4.821), followed by personal/family (4.392) and social factors (3.895). Pearson correlation shows significant positive relationships between mental health issues and both age (r = 0.416) and position (r = 0.398), with p < 0.05. The paper argues for the urgent need to strengthen mental health policies within policing institutions and contends that legal reform and administrative intervention are essential to safeguarding officers' psychological welfare.